2011
DOI: 10.1519/jsc.0b013e3181c1f79d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heat Exposure and 3% Dehydration Achieved Via Hot Water Immersion on Repeated Cycle Sprint Performance

Abstract: This study examined effects of heat exposure with and without dehydration on repeated anaerobic cycling. Males (n = 10) completed 3 trials: control (CT), water-bath heat exposure (∼39°C) to 3% dehydration (with fluid replacement) (HE), and similar heat exposure to 3% dehydration (DEHY). Hematocrit increased significantly from pre to postheat immersion in both HE and DEHY. Participants performed 6 × 15s cycle sprints (30s active recovery). Mean Power (MP) was significantly lower vs. CT (596 ± 66 W) for DEHY (56… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 27 publications
2
18
0
1
Order By: Relevance
“…Hematocrit increases and there is a decline in mean power and peak power during exercise as well as a greater level of perceived exertion (200). HOWI in warm water has been shown to increase total urinary Aquaporin 2 excretion suggesting elevation of plasma vasopressin levels (391).…”
Section: Head-out Water Immersion In Warm Watermentioning
confidence: 99%
“…Hematocrit increases and there is a decline in mean power and peak power during exercise as well as a greater level of perceived exertion (200). HOWI in warm water has been shown to increase total urinary Aquaporin 2 excretion suggesting elevation of plasma vasopressin levels (391).…”
Section: Head-out Water Immersion In Warm Watermentioning
confidence: 99%
“…Most previous studies which concluded that $3% loss of body mass impairs anaerobic performance, used exercise in heat (some in a heat chamber) to prompt body water loss (7,14,16,17,45). Kraft et al (21,22) used submersion in hot water bath. All participants completed performance tests on the same day of dehydration.…”
Section: Experimental Approach To the Problemmentioning
confidence: 99%
“…Similarly, as Kraft et al (22) found, heat exposure alone could diminish same day performance even when fluids are replaced at the rate of loss. Kraft et al (21,22) also included a recovery period allowing core temperature to return to near preheat exposure levels. Furthermore, residual effects of exercise-induced fatigue resulting from dehydration protocols may also impair subsequent performance.…”
Section: Experimental Approach To the Problemmentioning
confidence: 99%
See 2 more Smart Citations